Elucidating the phytochemical profile of Sophorae Flavescentis Radix-Astragali Radix herb pair: an integrated LC-QTOF-MS/MS, pharmacological activity, and network pharmacology study on anti-hepatocellular carcinoma effects - Yin, Yidi; Qu, Jiameng; Qu, Lanzhuo; Li, Zhiyuan; Xu, Huarong; Li, Qing (Frontiers in Chemistry, 2025)
BackgroundHepatocellular carcinoma (HCC) remains refractory because recurrence, drug resistance and systemic toxicity limit current therapeutics. The traditional herb pair Sophorae Flavescentis Radix-Astragali Radix (SF-AR) is reputed to counter liver disorders, but its anti-HCC potential and chemical basis have not been delineated.MethodsAnti-tumor activity was assessed in HepG2 cells and an H22 allograft mouse model. Constituents were characterized by high-performance liquid-chromatography–quadrupole time-of-flight mass spectrometry, and bioavailable prototypes were traced in rat plasma and organs. Absorbed molecules were linked to HCC-related targets through network pharmacology, and molecular docking examined their interactions to suggest potential target engagement.ResultsSF-AR suppressed HepG2 proliferation, abolished colony formation and induced dose-dependent apoptosis without harming L02 normal hepatocytes. Oral administration reduced H22 tumor burden in a dose-responsive manner without overt toxicity under the study conditions. Ninety-five constituents were delineated, encompassing 37 flavonoids, 23 alkaloids, 12 terpenoids, and organic, amino and nucleic acids; class-specific collision-induced dissociation pathways were summarized, including RDA cleavages for isoflavonoids and diagnostic ions for matrine-type alkaloids. Following oral administration, twenty-two prototype constituents were detected in rat plasma and were preferentially distributed to liver, kidney and spleen, confirming systemic exposure. Network pharmacology associated the absorbed constituents with potential HCC-related targets, and inflammation- and survival-related pathways were implicated as potential targets; favorable binding of representative constituents to these proteins was supported by molecular docking.ConclusionIntegrated pharmacological, chemical and computational evidence links the measurable anti-HCC efficacy of SF-AR to a bioavailable, multi-class phytochemical ensemble that converges on inflammation-driven survival pathways. SF-AR therefore emerges as a multi-target, low-toxicity therapeutic candidate that warrants further preclinical development for hepatocellular carcinoma.